ArchaeVir: A comprehensive genometrics database of archaeal viruses - Ojha, K.K.; Mishra, S.; Pandey, L.K. (Asian Network for Scientific Information, 2018)
Background and Objective: The era of high throughput sequencing technology has poured thousands of full genomes sequences in public databases. A remarkable portion of these genomic sequences belongs to the viruses of which viruses infecting archaea are least studied group. Archaeal viruses are morphologically more diverse than bacterial ones and display unique morphotypes. All sequenced archaeal viruses have DNA as their genetic material, which is double stranded in most of the cases. In this study, applied biometric method to understand the local and global feature of nucleotide distribution in all available archaeal genomes on Genbank. ArchaeVir database is dedicated to characterization of archaeal virus genomes with standardized genometrics of Z-curve and cumulative GC and AT skews. Material and Methods: All archaea viruses genomes were downloaded from NCBI. A script was written in MATLAB to calculate and plot the cumulative Z-curve and nucleotide skews. Database was created using MySQL and PHP, AJAX was used to create front end of the database. Results: Genometrics is a biometric analysis of chromosomes which is capable of identifying, at the level of whole genomes, features inherent to chromosome organization and functioning. This database also hosts the basic genomic records like genome length, GC%, total genes and proteins all sequenced viral genomes of archaea. In addition to this, two tools, one for finding the repeats and nucleotide distribution and second for plotting the geometric skew of nucleotide sequence has also been integrated with this database. Conclusion: Genometrics data of archaeal viruses available on the database could be readily accessed by the scientific community for further analysis of local and global features of viral genomes as well as for tutorial purpose. © 2018 Krishna Kumar Ojha et al.
Keywords: Z-curve; nucleotide skew, BLOB; DNA walk; Archaeal viruses